Knowledge of Sex Education and Human Immunodeficiency Virus Status: A Descriptive Study in Alhajuela, Ecuador - Bone, Karla S.; Fernández, Marcos A.; Moreira, Alison N.; Pérez, Karel Fernández (PT. Riset Press International, 2026)
Human Immunodeficiency Virus (HIV) continues to be a global public health problem. In rural communities such as Alhajuela, the lack of comprehensive sex education is a factor that contributes to the spread of the virus. This essay has a descriptive cross-sectional study was conducted in the parish of Alhajuela, Portoviejo, between October 2024 and March 2025, with interviews with health personnel and surveys of 60 residents. The result show a prevalence of 0.45%, higher than the national average (0.27%). Seventy percent of cases were men, and the most affected groups were young adults between the ages of 18 and 39. Thirty-eight-point three percent of respondents had a low level of knowledge about sex education. The study concludes that there are significant deficiencies in sexual health education, which increases vulnerability to HIV in the community. Comprehensive sex education programs and accessible prevention strategies are needed to strengthen the population´s capabilities.